The burden of testicular cancer from 1990 to 2019 in the Middle East and North Africa region - Safiri, Saeid; Hassanzadeh, Kamaleddin; Janbaz Alamdary, Sina; Mousavi, Seyed Ehsan; Nejadghaderi, Seyed Aria; Sullman, Mark J. M.; Naghdi-Sedeh, Nima; Kolahi, Ali-Asghar (Frontiers in Oncology, 2023)
Background The incidence rate of testicular cancer has risen in many countries during recent decades. This study aimed to outline the impact of testicular cancer on the Middle East and North Africa (MENA) region from 1990 to 2019, examining its burden by age group and according to the socio-demographic index (SDI). Methods Data on the incidence, death, and disability-adjusted life-years (DALYs) due to testicular cancer were retrieved from the Global Burden of Disease study 2019. The counts and age-standardized rates (per 100,000) were reported, and all rates were accompanied by 95% uncertainty intervals (UIs). Results In MENA, the age-standardized incidence rate of testicular cancer was 1.4 per 100,000 in 2019, showing a 244.0% increase since 1990. Similarly, the annual death rate, at 0.1, experienced a 2.6% rise during the same period. In 2019, testicular cancer accounted for 31.1 thousand DALYs, marking an age-standardized rate of 5.0, which was 2.8% higher than in 1990. The 1-4 age group exhibited the largest incidence rate in 2019. In addition, in both 1990 and 2019 the MENA/Global DALY ratio was higher than one in the 1-14 year age groups. During the period 1990 to 2019, the age-standardized DALY rate of testicular cancer steadily rose with higher SDI values, except for a decrease observed at an SDI of 0.8. Conclusion Over the last thirty years, there has been a notable rise in the burden of testicular cancer in the MENA region.